а) 2х + 3 = 3х - 2 б) 3 * ( 5 - х) = 11 + 2х
3 + 2 = 3х - 2х 15 - 3х = 11 + 2х
х = 5 15 - 11 = 2х + 3х
Проверка: 4 = 5х
2 * 5 + 3 = 3 * 5 - 2 х = 4 : 5
13 = 13 х = 0,8
Проверка: 3(5 - 0,8) = 11 + 2 * 0,8
15 - 2,4 = 11 + 1,6
12,6 = 12,6
N51)= (a²-b²)-(a-b)= (a-b)(a+b)-(a-b)= (a-b)(a+b-1) 2)=(4m²-n²)+(4m-2n)=
=(2m-n)(2m+n)+2(2m-n)=(2m-n)(2m+n+2)
3)=(x²-y²)-(x+y)=(x-y)(x+y)-(x-y)= (x-y)(x+y-1)
5)=(с²-d²)+(c+d)=(c+d)(c-d)+(c+d)=(c+d)(c-d+1)
N1) 1)=9(a²-1)=9(a-1)(a+1) 2)=2m(1-m²)=2m(1-m)(1+m) 3)=x²(1-x²)=x²(1-x)(1+x)
4)= y³(1-y²)=y³(1-y)(1+y) 5)m(x²-y²)=m(x+y)(x-y)
N2) 1)=(x²-1)(x^4+x²+1)=(x-1)(x+1)(x^4+x²+1) 2)=2(x³-8)=2(x-2)(x²+2x+4)